Do Prestigious Schools Still Exist in Padang? An Exploratory Study on State Junior High School Admission 2025 in Padang - Dodi Vionanda; Raihan Attaya Wood; Amelia Susrifalah (Rangkiang Mathematics Journal, 2025)
In this study, we perform an exploratory study of New Student Admission datasets for public Junior High School in Padang in 2025. We utilized tables, barplots, and boxplots to present information contained in datasets and we carried out cluster analysis using HDBSCAN algorithm. For this study we made use of admitted students’ datasets for each admission pathway of all state Junior High Schools in Padang in 2025. We carried out this study to investigate the emergence of prestigious schools among public Junior High School in Padang amid the implementation on zoning system. Our study reveals the presence of group of prestigious schools along with group of schools that admitted students mostly live nearby the schools. Hence, it is recommended for Padang Municipal government to improve the quality of schools that are not considered as prestigious schools since there are many schools that admitted students mostly live nearby the school.